PEMAKAIAN BAHASA INDONESIA (EJAAN) DALAM SURAT RESMI/DINAS KE LUAR DESA KESIMAN KERTALANGU KECAMATAN DENPASAR TIMUR DENPASAR - I Nengah Mileh (Universitas Warmadewa, 2018)
[Title: The Use of Indonesian Language (Spelling) in the Official Outgoing Letters of Kesiman Kertalangu Village, district of Denpasar Timur, Denpasar]. The use of Indonesian language, especially the use of spelling in the official outgoing letters of Kesiman Kertalangu Village, district of Denpasar Timur, Denpasar, is still a lot of mistakes. In this research, the object of research is the spelling errors in Indonesian language. This research applied observation method and note-taking technique to collect the data, synchronic descriptive qualitative method was used to present the result of the analisis combined with inductive technique. In this research, some spelling errors were found. The errors found in the official outgoing letters of Kesiman Kertalangu village are error in using final stop (.), comma (,),hyphen (-), a slash (/), a colon (:), and error in using capital letters.